(9x+7)-(3x-2)=

Simple and best practice solution for (9x+7)-(3x-2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9x+7)-(3x-2)= equation:


Simplifying
(9x + 7) + -1(3x + -2) = 0

Reorder the terms:
(7 + 9x) + -1(3x + -2) = 0

Remove parenthesis around (7 + 9x)
7 + 9x + -1(3x + -2) = 0

Reorder the terms:
7 + 9x + -1(-2 + 3x) = 0
7 + 9x + (-2 * -1 + 3x * -1) = 0
7 + 9x + (2 + -3x) = 0

Reorder the terms:
7 + 2 + 9x + -3x = 0

Combine like terms: 7 + 2 = 9
9 + 9x + -3x = 0

Combine like terms: 9x + -3x = 6x
9 + 6x = 0

Solving
9 + 6x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 6x = 0 + -9

Combine like terms: 9 + -9 = 0
0 + 6x = 0 + -9
6x = 0 + -9

Combine like terms: 0 + -9 = -9
6x = -9

Divide each side by '6'.
x = -1.5

Simplifying
x = -1.5

See similar equations:

| 9a+3b+c=4 | | 12-10x=122-45x | | 8y+7=-6y+2 | | 10+4x=3(7x-4)+5x | | -21p^2-24p=12 | | (-x^5)(-x)= | | 10x+2=-2+4 | | 2kx*2kx=0 | | (3x+9)+(6x+7)= | | 5x+10=4x+15 | | 6x+10y+11=0 | | x^2+2kx-7=0 | | -10p+3(8+8n)=-6(n-4) | | 137-5x=-58-8x | | 5x+9=39-7x | | 3y(5y+9)=0 | | 63-6x=9+18 | | 5x-3(x-10)=100-2(3x+5) | | 2(g+6)=24 | | .83=-.4b+.33b | | 5(g+6)=24 | | 3(x^2+4x+4)=0 | | n+8m=d | | 30n=-5 | | x=42*7 | | 2x(x-1)=5(x+3) | | 2x^3-11x^2+22x-15=0 | | 5x+31=14x-92 | | 945000+x=10x | | X^3-2x^2+3x+4=0 | | 5x-3(x-2)=30-3(x+3) | | 0.2x^2-80x+2500=0 |

Equations solver categories